1999
DOI: 10.2307/3580211
|View full text |Cite
|
Sign up to set email alerts
|

The Suppression of Metastases and the Change in Host Immune Response after Low-Dose Total-Body Irradiation in Tumor-Bearing Rats

Abstract: We have shown that metastasis is suppressed by low-dose total-body irradiation (TBI) in tumor-bearing rats. We have evaluated the immunological effects of low-dose TBI. Total-body irradiation with 0.2 Gy was given 14 days after the implantation of 5 x 10(5) allogenic hepatoma cells (KDH-8) which produce transforming growth factor beta (TGF-beta). On day 21, the splenocytes and tumor-tissue infiltrating lymphocytes were analyzed by FACScan and RT-PCR for the mRNA of the genes that encode tumor necrosis factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 22 publications
5
97
0
1
Order By: Relevance
“…Th1 cytokines are involved in inflammatory reactions including activation of macrophages and T cells, whereas Th2 cytokines stimulate humoral and allergic responses of the immune system. This imbalance between Th1 and Th2 cytokines production was involved in the long-term side effects in people who were exposed to radiation (Hashimoto et al 1999;Emerit et al 1995;Kusunoki et al 2010;Kusunoki and Hayashi 2008;Bower et al 2002Bower et al , 2009). …”
Section: Immunogenicity Of Ionizing Radiationmentioning
confidence: 99%
“…Th1 cytokines are involved in inflammatory reactions including activation of macrophages and T cells, whereas Th2 cytokines stimulate humoral and allergic responses of the immune system. This imbalance between Th1 and Th2 cytokines production was involved in the long-term side effects in people who were exposed to radiation (Hashimoto et al 1999;Emerit et al 1995;Kusunoki et al 2010;Kusunoki and Hayashi 2008;Bower et al 2002Bower et al , 2009). …”
Section: Immunogenicity Of Ionizing Radiationmentioning
confidence: 99%
“…In one report, lowdose irradiation following transplantation of a hepatoma cell line in a rat model resulted in an increased proportion of CD8-positive splenocytes, increased numbers of tumor infiltrating lymphocytes, increased TNF-a and IFN-g expression and decreased TGF-b expression. This response correlated with a reduction in metastases (Hashimoto et al, 1999). Another study demonstrated an increased CD4:CD8 T cell ratio, and decreased expression of TGF-b and VEGF following low-dose total body-irradiation, which correlated with delayed tumor growth in mice transplanted with the Lewis lung carcinoma cell line (Miller et al, 2003).…”
Section: Enhancement Of Antitumor Effector Mechanismsmentioning
confidence: 84%
“…A number of factors may explain why the consistent characterization of immune responses to radiation remains elusive including differences in radiosensitivity or reactivity of different cell and tissue types, and dose-dependent effects. The latter have been explored in a number of studies, some of which suggest that lower doses of radiation have a greater potential to enhance immune responses (Hashimoto et al, 1999;Cao et al, 2002;Ina and Sakai, 2005;Shigematsu et al, 2007).…”
Section: Revisiting the Role Of Radiationmentioning
confidence: 99%
“…The occurrence of this transient increase in liver enzymes cannot therefore be easily explained. Experimental data showed that LTBI can induce a degree of immune stimulation (17) in various animal models (18). Very few human data suggest that similar effects may be seen in humans (19).…”
Section: Discussionmentioning
confidence: 99%